The Functional Significance of Synaptotagmin Diversity in Neuroendocrine Secretion - Moghadam, Paanteha K.; Jackson, Meyer B. (Frontiers in Endocrinology, 2013)
Synaptotagmins (syts) are abundant, evolutionarily conserved integral membrane proteins that play essential roles in regulated exocytosis in nervous and endocrine systems. There are at least 17 syt isoforms in mammals, all with tandem C-terminal C2 domains with highly variable capacities for Ca2+ binding. Many syts play roles in neurotransmitter release or hormone secretion or both, and a growing body of work supports a role for some syts as Ca2+ sensors of exocytosis. Work in many types of endocrine cells has documented the presence of a number of syt isoforms on dense-core vesicles containing various hormones. Syts can influence the kinetics of exocytotic fusion pores and the choice of release mode between kiss-and-run and full-fusion. Vesicles harboring different syt isoforms can preferentially undergo distinct modes of exocytosis with different forms of stimulation. The diverse properties of syt isoforms enable these proteins to shape Ca2+ sensing in endocrine cells, thus contributing to the regulation of hormone release and the organization of complex endocrine functions.